Physiological studies on Alternaria porri and Stemphylium vesicarium causing purple blotch complex in onion - Yadav, Ritesh Kumar; Sandeep Jain, Amarjit Singh,; Pandit, Madhav; Dhakal, Rajeev (Horticultural Biotechnology Research)
Effect of different culture media, pH levels and natural substrates on mycelial growth and sporulation of Alternaria porri and Stemphylium vesicarium, incitants of purple blotch complex of onion was investigated. Maximum colony growth of A. porri and S. vesicarium was recorded on oat meal agar and Richard’s agar while, oat meal agar and V8 juice agar recorded the maximum sporulation, respectively. Similarly, pH 5.0 and 6.0 on potato dextrose agar (PDA) recorded the maximum colony growth of A. porri and S. vesicarium, respectively. None of the pH levels on PDA supported the sporulation of A. porri while maximum sporulation of S. vesicarium was recorded on pH 5.0. Onion seed stalks and garlic leaves were found to be the most suitable natural substrates for mass multiplication of A. porri and S. vesicarium, respectively. The present findings are useful for preparation of inoculums required for resistance breeding and fungicidal evaluation against purple blotch complex.